The Impact of AFT on Export Performance of Selected Asian Developing Countries - Mowlaei, Mohammad (Asian Development Policy Review, 2017)
By liberalizing trade and capitalizing on areas of comparatives advantages, the developing countries can benefit economically. There are a lot of obstacles which constraints the ability of countries to engage in international trade. Aid-for-Trade (AFT) is a part of overall Official Development Assistance (ODA)-which helps developing countries to build their trade in global markets. This paper employs System-GMM technique to examine whether AFT helps Asian aid-receiving countries to improve their export performance over the period 2000-2015. The results show a positive and significant effect of AFT in multiple measures of export performance. However, the aids should be targeted and avoid any misusing.